Theoretical Foundations of the Development of Modern Civil Society Institutions in a Democratic Legal State - Batirovich, Masharipov Ikramjon (Research Parks Publishers, 2023)
The management of the state and society is complex and various management models and forms of management have been developed, the process of building a modern civil society, certain specific features have been analyzed, as well as effective cooperation between non-governmental non-commercial organizations, political parties, self-government bodies and state local authorities. based on increasing the level, development of civil society institutions and ensuring their independence from state bodies, the author's comments on full-fledged management were formed.